2009
DOI: 10.1016/j.seizure.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on aetiology based outcome of infantile spasms

Abstract: The aetiology and prognosis of infantile spasms is evolving. To improve outcome, we need to reduce the delay to diagnosis and develop prospective double-blind randomized clinical trials looking at not only the epileptic outcome but also cognitive outcome of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
6
54
1
6
Order By: Relevance
“…Although several reports showed that the patients who had cryptogenic etiology responded better to TPM than did the symptomatic patients18,31,32), different results were also reported28,33). In our study, 4 of 7 cryptogenic patients had complete disappearance of spasms and hypsarrhythmia, and 6 of 7 cryptogenic patients (85%) achieved a ≥50% reduction in seizure frequencies.…”
Section: Discussioncontrasting
confidence: 62%
“…Although several reports showed that the patients who had cryptogenic etiology responded better to TPM than did the symptomatic patients18,31,32), different results were also reported28,33). In our study, 4 of 7 cryptogenic patients had complete disappearance of spasms and hypsarrhythmia, and 6 of 7 cryptogenic patients (85%) achieved a ≥50% reduction in seizure frequencies.…”
Section: Discussioncontrasting
confidence: 62%
“…The estimated incidence of WS is low, occurring in one out of 3-5000 live births, but its consequences are grave. Depending on the underlying etiology, the majority of infants remain with cognitive or neurodevelopmental deficits ( 50% -60% of infants with IS of unknown etiology; 84% -98% of infants with IS caused by structural/metabolic etiology) or persisting epilepsy, which is usually drug resistant (Baram et al 1996;Karvelas et al 2009;Pellock et al 2010;Auvin et al 2012;Vendrame et al 2012;Lee et al 2013).…”
Section: Animal Models Of Epileptic/is and West Syndromementioning
confidence: 99%
“…Significant interest was drawn toward targeting the mTOR pathway, given the association of several disorders of the mTOR pathway with IS. The classical genetic cause of mTOR overactivation, tuberous sclerosis, is diagnosed in 5% -10% of infants with IS, and 38% of infants with tuberous sclerosis have IS (Sidenvall and Eeg-Olofsson 1995;Curatolo et al 2001;Riikonen 2001;Karvelas et al 2009;Bombardieri et al 2010;Chu-Shore et al 2010;Osborne et al 2010). Mutations in pathways that cross talk and increase the activity of mTOR have been identified in patients with IS as a result of hemimegalencephaly or polyhydramnios, microcephaly, and symptomatic epilepsy (PMSE).…”
Section: Animal Models Of Early-life Epilepsymentioning
confidence: 99%
“…[98,99] Başta ACTH ve vigabatrin yardımıyla nöbet kontrolünün sağlan-ması LGS'ye progresyon oranını düşürmüştür. [100] Etiyolojiye göre değerlendirildiğinde, kriptojenik olguların %51'ine karşın, semptomatik olguların yalnızca %7'si normal gelişim göstermektedir. Bazı serilerde olguların yaklaşık %17'si LGS'ye dönüşmektedir.…”
Section: Eeg Bulgularıunclassified